2010
DOI: 10.3758/s13421-010-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

Following the standard form: Effects of equation format on algebraic modeling

Abstract: When people construct algebraic equations to represent quantitative relations, they often reverse the roles of the variables (6S = P instead of 6P = S). Results from three experiments show that a major reason for such reversal errors is people's adherence to, and interpretation of, the Standard Form of algebraic models. College students constructed, selected, and interpreted algebraic models that either had the standard multiplication format (MF: ax = y), or the mathematically equivalent division format (DF: y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 34 publications
7
42
0
1
Order By: Relevance
“…These may include images, conventionalized structures such as number lines, or candidate expression fragments adapted or selected from those previously encountered (Sherin, 2001;Fisher, et al, 2011). These simulations are made specific by a process of alignment: we suggest that structure mapping (Gentner, 1983) is used to identify entities in text or images with those in equations.…”
Section: Using the Structure Of Notations To Construct Equationsmentioning
confidence: 99%
See 3 more Smart Citations
“…These may include images, conventionalized structures such as number lines, or candidate expression fragments adapted or selected from those previously encountered (Sherin, 2001;Fisher, et al, 2011). These simulations are made specific by a process of alignment: we suggest that structure mapping (Gentner, 1983) is used to identify entities in text or images with those in equations.…”
Section: Using the Structure Of Notations To Construct Equationsmentioning
confidence: 99%
“…Recently, Fisher, et al (2011) demonstrated that the reversal rate of typical students-and-professors style problems sharply decreases when students are forced to use an equation structure that creates a high-quality alignment between text and equation. In their experiments, students were encouraged to construct division models such as for sentences such as "There are six students for every professor.…”
Section: The Left-right Transcription Heuristicmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have attributed student difficulty to a tendency for a "directtranslation" approach (Clement, 1982;Fisher et al, 2010;Hegarty et al, 1995;Wollman, 1983). This strategy is used when students attempt to make the sequence of algebraic symbols match the sequence of objects in a word problem.…”
Section: Direct Translation and Static Comparison Strategiesmentioning
confidence: 99%